A Bibliometric Analysis of Gene Mutations in Thalassemia: Research Trends, Knowledge Structure, and Emerging Themes - Henri Setiawan; Launa Lutfi Sania; Andan Firmansyah (Yayasan Inspirasi El Burhani, 2024)
Introduction: Thalassemia is an inherited blood disorder caused by impaired globin-chain production, with gene mutations playing a central role in its molecular basis and phenotypic diversity. The rapid expansion of genetic and genomic research has generated a broad and increasingly interconnected body of literature, making it important to characterize the development and structure of this research field. Objective: This study aimed to map research trends, knowledge structure, thematic patterns, and international collaboration in the field of gene mutations in thalassemia. Method: A bibliometric analysis was conducted using publications retrieved from PubMed on 20 August 2024. The search strategy was “gene mutation AND thalassemia” and was limited to publications from 2019 to 2024. Bibliographic data were analyzed using RStudio with the Biblioshiny application. Analyses included annual scientific production, relevant sources, Bradford’s Law, thematic mapping, keyword co-occurrence, and international collaboration. Result: The analysis demonstrated sustained research activity during 2019–2024, with the highest publication output in 2020 (213 publications). Hemoglobin was the most productive source, with 131 publications, followed by Annals of Hematology (30) and Hematology (23). Thematic and keyword analyses identified mutation, genotype, alleles, sequence analysis, α-thalassemia, β-thalassemia, genetic testing, prenatal diagnosis, fetal hemoglobin, and gene editing as major interconnected research areas. The collaboration analysis demonstrated broad international research networks involving countries across multiple regions. Conclusion: Research on gene mutations in thalassemia has developed from fundamental mutation and genotype characterization toward genetic diagnosis, prenatal applications, and emerging genomic therapeutic approaches. These findings highlight the importance of continued molecular research and international collaboration to support the translation of genomic knowledge into thalassemia prevention, diagnosis, and personalized care.